Role of indigo in improving the productivity of rainfed lowland rice-based cropping systems - Agustin, E.O.; Ortal, C.I.; Pascua Jr, S.R.; Sta. Cruz, Pompe C.; Padre, A.T.; Ventura, W.B.; Obien, S.R.; Ladha, J.K. (Cambridge University Press, 1999)
A long-term field experiment was conducted to determine the effects of indigo (Indigofera tinctoria) on the productivity of rainfed lowland rice-based cropping systems: rice–tomato, rice–tobacco or soyabean, rice–maize, and rice–garlic. Indigo was grown as an intercrop during the dry season and incorporated as green manure for wet season rice. Dry season crop yields were generally not affected by the indigo intercrop but indigo green manure had a positive effect on rice yields. At the same level of nitrogen (N) inputs, indigo-N produced higher yields than urea-N which may be due to high inorganic N losses.